1985
DOI: 10.1002/jcu.1870130604
|View full text |Cite
|
Sign up to set email alerts
|

Echogenic adnexal masses associated with first‐trimester pregnancy: Sonographic appearance and clinical significance

Abstract: In a retrospective survey of a large obstetrical ultrasound experience, 10 echogenic adnexal masses in nine patients with a coexistent intrauterine pregnancy were detected and analyzed. Definitive follow-up data available for seven of the nine patients disclosed three ovarian teratomas, two hemorrhagic corpus luteum cysts, one endometrioma, one inflammatory mass, and one colonic pseudomass. In one additional patient, an echogenic ectopic pregnancy with an intrauterine pseudogestational sac simulated the above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Therefore, only 12 HOCs in adult patients have been reported, along with references in general artides on pelvic masses [3][4][5][6]. In these studies it was shown that HOCs have a variety of sonographic patterns.…”
mentioning
confidence: 99%
“…Therefore, only 12 HOCs in adult patients have been reported, along with references in general artides on pelvic masses [3][4][5][6]. In these studies it was shown that HOCs have a variety of sonographic patterns.…”
mentioning
confidence: 99%
“…It is believed that whilst adnexal masses occur in roughly 1:800 pregnancies, the prevalence of ovarian cancers in pregnancy has been reported as 1:653 [11,12]. Thus, although rare, ovarian tumors must be considered as a cause of the symptoms mimicking an ectopic pregnancy presentation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 1 study involving 31 patients with adnexal masses in pregnancy, 19 underwent surgical management, and 2 were found to have hemorrhagic cysts 14 . Another small study followed 9 patients with echogenic adnexal masses in early pregnancy, of which 2 of 9 were determined to be hemorrhagic corpus luteum cysts based on follow-up ultrasound in one case and pathology of the cyst after laparoscopic removal in the other case 35 . Hemorrhagic cysts often resolve by 14 to 16 weeks' gestational age 26 …”
Section: Types Of Adnexal Masses In Pregnancymentioning
confidence: 99%